Current Approaches, Typologies and Predictors of Deviant Work Behaviors: A Scoping Review of Reviews - Zappalà, Salvatore; Sbaa, Maha Yomn; Kamneva, Elena V.; Zhigun, Leonid A.; Korobanova, Zhanna V.; Chub, Anna A. (Frontiers in Psychology, 2022)
This study provides a scoping review of the recent conceptual developments about the deviant work behavior and counterproductive work behavior constructs. It also examines the specific types of deviant work behavior that have been more consistently investigated in the last decade, and whether they cover the interpersonal or organizational type of deviant behavior. In addition, individual, group, and organizational predictors of deviant work behaviors are examined. A scoping review of reviews was conducted on Scopus and Web of Science databases and 54 studies published from 2010 to June 2021 were taken into account. Results show that more recent conceptualizations are based on well established models in the literature and consider the hierarchical structure of these two constructs. Recent reviews examine the relationships of deviant work behavior with job performance and ethical behavior constructs, the multilevel nature of deviant work behavior, and the consequences for the actor of the deviance. The specific types of deviant work behavior more frequently reviewed in the last decade are workplace abuse, incivility, ostracism, bullying and sexual harassment, and abusive and destructive leadership; this evidence suggests a much greater attention devoted to interpersonal, rather than organizational, forms of deviant work behavior. Regarding antecedents, results show the continuing prevalence of personality factors antecedents. Limitations of the study and theoretical and practical implications for the field are also provided.